Evaluation of Potential Drug-Drug Interactions and Association with Adverse Drug Reactions in Predialysis Chronic Kidney Disease Patients at Indonesian National Referral Hospital - Triasti Khusfiani; Vivian Soetikno; Ni Made Hustrini; Nafrialdi Nafrialdi (Acta Medica Indonesiana)
Background: Chronic kidney disease (CKD) is often accompanied by a variety of comorbidities that require several medications thus, polypharmacy is unavoidable. One of the consequences of polypharmacy is the occurrence of potential drug-drug interactions (DDI). The aim of this study is to evaluate the profile of DDI in pre-dialysis CKD patients and to identify the possible adverse drug reactions (ADR) due to DDI. Methods: This cross-sectional study includes stage 3-5 pre-dialysis CKD patients at a referral hospital in Indonesia in 2019 – 2020. Data were collected from the electronic health record and the hospital’s medical record. The prescriptions were analysed for potential DDI using Micromedex software and ADRs assessment through clinical symptoms and laboratory data abnormalities. Results: A total of 106 patients were included in the study, around 60 (56.6%) patients received more than six medications. There were 111 types of medications prescribed with the most frequently prescribed drug was bisoprolol (36.5%). The proportion of patients who received treatment with a potential DDI was 76% (81 patients), while the proportion of patients who experienced ADR was 28% (23 patients). The most prevalent ADRs were hyperglycaemia, hypertension, hyperkalaemia, and hypotension. Cardiovascular disease had a statistically significant relationship with ADR suspected due to DDI (p = 0.03). Conclusion: A significant number of potential DDI were seen in the prescriptions of stage 3-5 pre-dialysis CKD patients at a referral hospital in Indonesia between 2019 – 2020. Cardiovascular disease was identified as the most common risk factor for ADR suspected caused by DDI.